Identifikasi Kandungan Pupuk Organik Cair dari Hidrogel Limbah Diapers Terhadap Penambahan Spirulina platensis - Rasyidah Rasyidah; Irda Nila Selvia; Devi Siruwahni (Program Studi Pendidikan Biologi, 2022)
The increase of the number of babies birth will also increase the use of baby diapers. The increase of use diapers is not matched by the act of treating the diaper waste. Whereas diaper waste often becomes an environmental problem. Diaper waste has the potential to be used as organic liquid fertilizer because it contains nitrogen, electrolyte ions, and dissolved hormones from urine. But the decomposition process takes a very long time if the diapers are just left intact without being given certain treatment to separate the gel and plastic parts of the diaper. So it is necessary to carry out a recycling process involving microbes so that the decomposition process of organic matter from diaper waste can take place optimally. One of the microalgae that can be used is Spirulina platensis. Therefore, this study aims to determine the content of liquid organic fertilizer produced from composting diaper waste with the addition of Spirulina platensis. The study was conducted using an experimental method with 3 treatments, namely control (0 ml S. platensis+3 kg hydrogel), D2 (25 ml S. platensis+3 kg hydrogel), D3 (50 ml S. platensis+3 kg hydrogel). Parameters observed were macro nutrients (C-Organic, Total Nitrogen, Phosphorus), and C/N Ratio. Data analysis was carried out by looking at the C-organic, N, P, K and C/N ratio content in liquid organic fertilizer obtained from the addition of Spirulina platensis through laboratory tests at the initial and final stages of composting. From the results of the analysis it was found that the macro nutrient content in the form of elements N, P, K and the C/N ratio at the final stage of composting did not show a value that suitable with technical requirements for liquid organic fertilizer according to Minister of Agriculture No. 70 of 2011. So that in its application, use hydrogel diapers as an organic fertilizer, it can still be combined with other organic materials to meet the required nutrients.